THE NOTION OF "CONCEPT" IN LINGUISTICS AND ITS ROLE IN THE PRINCIPLES OF ANTHROPOCENTRISM AND LINGUO-CULTURAL STUDIES - Khushmanova Shakhnoza Ibragimovna (Modern American Journals, 2025)
The article attempts to examine the structurally ambivalent concept of "concept" in the field of linguistics, and particularly its role in the large subject of anthropocentrism and study of linguoculture.Concepts form the basis of cognitive and semantic units for us human beings and give us the ability to categorize and communicate the real world. At its most extreme, an anthropocentric approach sees people as the makers of meaning. It is concerned with the integration of physical experience and socio-cultural interaction.
Keywords: Concept, linguistics, anthropocentrism, linguo-cultural studies, Uzbek language, semantics, cognition, culture